The muscular ability of the two legs and its relationship to some basic skills of handball - Abod, Zahraa Fadel; AlHaddad, Noor Hatem (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to identify the relationship between the muscular abilities of the two legs and the performance of those skills among the research sample. The researchers used the descriptive approach to suit the nature of the problem to be investigated. As for the research sample, it was represented by 16 handball players of the Beish Merka Handball Club. The data was processed through the Statistical Package for the Social Sciences (SPSS). The results of the study showed that there is a statistically significant relationship between the muscular abilities of the two legs, the strength speed of the legs and Sargent’s vertical jump test (p < 0.05). The relationship obtained from the results of the research is direct, that is, whenever the muscular capabilities of the two legs are high, the performance in the skill tests is also high and vice versa. Therefore, the researchers recommend the development of exercises specific for the muscular abilities of the two legs to develop the basic skills of handball.